EVALUACIÓN Y RETROALIMENTACIÓN POR WIRIS QUIZZES EN EL CAMPO DE LA INGENIERÍA - Edgar M. Marín Ballón (2021)
Faced with the change to the virtual teaching modality due to the COVID-19 pandemic, teachers have the obligation to prepare competent, critical and autonomous professionals who can respond to various situations and face challenges once they occupy their workspace, all this within the framework of virtual teaching. Assessment is one of the aspects that changed the most with this transition to virtual mode, and although learning platforms such as Moodle or Blackboard have different options for creating questions, sometimes these are not enough, especially in engineering and science courses. That is why it is required to use programs such as Wiris, which provides various tools for formulating questions. Considering this, this article aims to describe the main tools that Wiris offers in formulating questions and designing evaluations, in addition to showing the effectiveness of automatic feedback through this tool in formative assessment. With this objective, it is discussed about advantages, limitations, and difficulties that teachers can find in the application of this powerful tool.